ANALISIS KESALAHAN PENULISAN PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V DIGITAL DI MIN 4 KOTA LHOKSEUMAWE - Suci Ratulmuna; Samsul Bahri; Zainal Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing is one of the most complex language skills because it requires students to apply spelling rules accurately and consistently. This study aims to describe the forms of writing errors made by fifth-grade students of the Digital Class at MIN 4 Kota Lhokseumawe, to identify the factors that cause these errors, and to describe the efforts made by the teacher to correct them. This research used a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with the class teacher, and documentation of 17 students' procedural texts, and were analyzed using the Miles and Huberman model of data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation as well as member checking. The results show that 133 writing errors were found and classified into five categories: spelling errors (41 errors, 30.8%), punctuation errors (26 errors, 19.5%), non-standard word errors (25 errors, 18.8%), capitalization errors (22 errors, 16.5%), and preposition errors (19 errors, 14.3%). The errors were caused by internal factors, such as low motivation to reread written work and limited reading habits, and external factors, such as habitual use of informal spoken Indonesian and heavy exposure to digital chat abbreviations, which proved more influential than regional language interference. The teacher has made various efforts, including direct explanation, direct and indirect correction, corrective feedback, habituating self-checking, and continuous writing practice, although these efforts still need to be intensified and integrated with literacy habituation at school and at home.